Research as an integral component of biology education in Philippine schools - Castillo, Josefino R. (Animo Repository, 2012)
This paper examines the progress of Biology education in the Philippines over two decades. A lack of laboratory equipment and funds were some factors students had to contend with. The study highlights current Philippine colleges and universities which place a high premium on performance rating measured in terms of outputs in academic and professional organizations. One example was the University of Santo Tomas which had integrated research into the curriculum. Under-graduate students are required to undertake experimental research under the supervision of faculty members and to present the research work to a panel, as a requirement for graduation. Most studies focus on the testing medicinal plants against parasites, and human diseases, such as diabetes, hypertension, and cancer. Other fields for student project work include allergy, immunology, molecular systematics, and bioinformatics. Insufficient number of animal models and small sample size for a statistically robust research are factors impeding the progress and development of research and development and Biology education in the country.